Nivel de conocimiento en manejo de residuos sólidos y actitudes hacia la conservación ambiental en vendedoras de pescado de la asociación de pescadores artesanales de Requena 2022 - Sánchez Hidalgo, Sandra Milagros (2024)
En this research aimed to determine the relationship between the level of knowledge in solid waste management and the attitude towards environmental conservation among female fish vendors of the Artisanal Fishermen's Association of Requena, located in the market called "Casona de Pescadores" in the city of Requena, District of Requena 2022. The study was quantitative, simple relational, and non-experimental in design. The target population for the study consisted of all vendors in that market in the year 2022, and the sample size was 70 residents. Inclusion and exclusion criteria were considered using the survey technique, and two questionnaires with ten and fifteen items each were used as the applied instruments, which were validated through Aiken's Validity Index and tested for reliability using Cronbach's Alpha and Pearson's r for split-half reliability. The data were analyzed, processed, and tabulated using the SPSS v27 statistical package. The results indicate that the level of knowledge in solid waste management among the fish vendors of APA Requena is rated as regular to low. Similarly, the level of knowledge in solid waste management according to age group and educational level is rated as regular to low. The overall, cognitive, affective, and reactive attitudes towards environmental conservation were neutral to unfavorable. There is a significant, direct, and intense relationship between the level of knowledge in solid waste management and the general attitude towards environmental conservation among fish vendors of APA Requena at a probability level of 0.05.